Sedimentary biogeochemical data from a mussel farm in As Vig, Denmark - Hylén, Astrid; Taylor, Daniel; Kononets, Mikhail; Lindegarth, Mats; Stedt, Anna; Bonaglia, Stefano; Bergström, Per (University of Gothenburg, 2021)
The goal of the study was to evaluate how a newly re-established mussel farm in As Vig, Denmark, affected the sediment-water nutrient exchange. A mussel farm and a reference site were sampled on four occasions in two years, spanning the entire first year of production. Nitrate reduction rates and sediment-water fluxes of nutrients, methane, dissolved inorganic carbon and oxygen were measured in situ with benthic chamber landers. Sediment cores were collected for measurements of carbon, nitrogen and pigments and sedimentation rates were measured with sediment traps. Currents, illuminance at the seafloor and water column profiles of salinity, temperature and chlorophyll a were measured to describe the environmental characteristics of the stations.

The dataset contains 8 files with the following data:
- CTD profiles and chlorophyll a concentrations in the water column
- Current speed and current directions
- Illuminance at the sediment surface
- Sedimentation rates (total, organic matter, inorganic matter)
- Sediment-water fluxes of oxygen, nutrients, methane and dissolved inorganic carbon
- Nitrate reduction rates in the sediment
- Sedimentary pigment content (chlorophyll a, fucoxanthin, pheopigments)
- Carbon and nitrogen in the sediment solid phase, porosity

Full descriptions of the data can be found in the corresponding readme files accessible from the Description tab.

Studiens mål var att utvärdera hur en nyligen återetablerad musselodling i As Vig, Danmark, påverkade utbytet av närsalter mellan sediment och vatten. Se utförlig beskrivning på engelska.

Datasetet innehåller 8 filer med följande data:
- CTD-profiler och klorofyll a-koncentrationer i vattenpelaren
- Strömhastigheter och strömriktningar
- Ljusmätningar vid havsbotten
- Sedimentationshastigheter (total, organiskt material, oorganiskt material)
- Sediment-vattenflöden av syre, närsalter, metan, och löst oorganiskt kol
- Nitratreduktionshastigheter i sedimentet
- Pigmentinnehåll i sedimentet (klorofyll a, fukoxantin, pheopigment)
- Kol och kväve i sedimentets fasta fas, porositet

Utförlig beskrivning av data finns i de tillhörande readme-filerna under fliken Beskrivning.
Sedimentära biogeokemiska data från en musselodling i As Vig, Danmark
Keywords: NUTRIENTS; SEDIMENT CHEMISTRY; AQUACULTURE; EUTROPHICATION; BENTHIC; MUSSELS; mussel farming; musselodling; Environmental Sciences; Miljövetenskap; Geochemistry; Geokemi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Fish and Aquacultural Science; Fisk- och akvakulturforskning